DJC Suppresses Advanced Glycation End Products-Induced JAK-STAT Signaling and ROS in Mesangial Cells. (29th May 2017) - Sun, Min; Li, Yan; Bu, Wenjie; Zhao, Jindong; Zhu, Jianliang; Gu, Lingling; Zhang, Pingping; Fang, Zhaohui
Abstract : The antidiabetic properties and anti-inflammatory effects of Danzhi Jiangtang Capsules (DJC) have been demonstrated in clinical and laboratory experiments. In this study, we explored whether DJC can ameliorate advanced glycation end products- (AGEs-) mediated cell injury and the precise mechanisms of DJC in treating diabetic nephropathy (DN). Western blot analysis was employed to assess the expressions of iNOS, COX2, and SOCS and the phosphorylation of JAK2, STAT1, and STAT3 in glomerular mesangial cells (GMCs) after treatment with DJC. TNF- α, IL-6, and MCP-1 were determined using double-antibody sandwich ELISA. ROS and NADPH oxidase activity were measured by DCFH-DA assay and lucigenin-enhanced chemiluminescence, respectively. DJC significantly reversed the AGEs-induced expression of COX2 and iNOS. Moreover, DJC inhibited the AGEs-induced JAK2-STAT1/STAT3 activation, resulting in the inhibition of inflammatory cytokines such as IL-6, MCP-1, and TNF- α in a concentration-dependent manner. The ability of DJC to suppress STAT activation was also verified by the observation that DJC significantly increased the SOCS3 protein level. DJC reversed the AGEs-induced accumulation of ROS and NADPH oxidase activity, thus confirming that DJC possesses antioxidant activity. The results suggest that the anti-inflammatory effects of DJC in GMCs may be due to its ability to suppress the JAK2-STAT1/STAT3 cascades and reduce ROS production.